Miscellaneous Pieces - Bunyan, John, 1628-1688 (Salt Lake City, UT : Project Gutenberg, 2003)
"Miscellaneous Pieces by John Bunyan" is a collection of theological writings produced in the late 17th century. This compilation delves into various aspects of the Christian faith, offering insights into topics such as the Trinity, the relationship between law and grace, the nature of sin, and reflections from Bunyan's last days. It serves as both a devotional work and a guide for believers seeking a deeper understanding of their spiritual journey. The book is structured around several key pieces, including essays on the Trinity and the Christian experience, where Bunyan provides comforting guidance for those unsettled in their faith. In discussing the law, he contrasts the experiences of believers and non-believers, revealing that believers are no longer under the law$1 (Bs condemnation but are instead guided by grace. Bunyan's final sermon elucidates the necessity of being born of God, emphasizing that true salvation comes not from human effort but from divine grace. His heartfelt reflections on sin, prayer, and the joys and terrors of the afterlife offer a compelling testament to his devout Christian belief and serve as a source of encouragement for readers grappling with their own faith. (This is an automatically generated summary.)s
Of the Trinity and a Christian -- Of the Law and a Christian -- Bunyan's Last Sermon -- Bunyan's Dying Sayings.
Release date is 2003-01-01
Transcribed from the 1845 Thomas Nelson (3z(BWorks of the Puritan Divines (Bunyan)(3y (Bedition by David Prices
Keywords: Christianity